Pictures on water, or identity in the modern world (Journal of Philosophy Culture and Political Science, 2019)
In this article, sights at a problem of identity of the person in the modern world are being analyzed. Identity is a problem of experience and a reﬂ ection, self-understanding, self-comprehension of as complete person in itself and in different contexts, references of to those or other cultures and to movements, systems of values, ideas and representations. This phenomenon is often discussed by experts of a postmodern epoch